Low-Dose Methylmercury-Induced Apoptosis and Mitochondrial DNA Mutation in Human Embryonic Neural Progenitor Cells. (21st July 2016) - Wang, Xinjin; Yan, Mengling; Zhao, Lina; Wu, Qing; Wu, Chunhua; Chang, Xiuli; Zhou, Zhijun
Abstract : Methylmercury (MeHg) is a long-lasting organic pollutant primarily found in the aquatic environment. The developing brain is particularly sensitive to MeHg due to reduced proliferation of neural stem cell. Although several mechanisms of MeHg-induced apoptosis have been defined in culture models, it remains unclear whether mitochondrial DNA (mtDNA) mutation is involved in the toxic effect of MeHg, especially in the neural progenitor cells. In the present study, the ReNcell CX cell, a human neural progenitor cells (hNPCs) line, was exposed to nanomolar concentrations of MeHg (≤50 nM). We found that MeHg altered mitochondrial metabolic function and induced apoptosis. In addition, we observed that MeHg induced ROS production in a dose-dependent manner in hNPCs cells, which was associated with significantly increased expressions of ND1, Cytb, and ATP6. To elucidate the mechanism underlying MeHg toxicity on mitochondrial function, we examined the ATP content and mitochondrial membrane potential in MeHg-treated hNPCs. Our study showed that MeHg exposure led to decreased ATP content and reduced mitochondrial membrane potential, which failed to match the expansion in mtDNA copy number, suggesting impaired mtDNA. Collectively, these results demonstrated that MeHg induced toxicity in hNPCs through altering mitochondrial function and inducing oxidative damage to mtDNA.